2004
DOI: 10.2466/pr0.95.7.771-779
|View full text |Cite
|
Sign up to set email alerts
|

How Is Stigmatization Affected by the 'Layering' of Stigmatized Conditions, Such as Serious Mental Illness and Hiv?

Abstract: Vignettes were used to examine the effect of labeling a person with two stigmatized illnesses, HIV disease and serious mental illness (schizophrenia). The additive model predicted that stigma associated with combined HIV and serious mental illness would resemble the simple sum of those for the two conditions. The discounting model predicted that the presence of serious mental illness would lead subjects to view the target individual as less responsible for infection, resulting in less stigmatization than given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As mentioned previously, the vignettes were designed to depict the modal gender and symptom profile, average age range of onset, most common treatment, and usual prognosis for each target individual. Second, vignette methodologies are widely employed in the stigma literature (e.g., Ben Porath, 2002;Corrigan et al, 2005;McBride, 1998;Schumacher, Corrigan, & Dejong, 2003;Schwartz, Weiss, & Lennon, 2000;Walkup, Cramer, & Yeras, 2004), rendering the results of the present study readily comparable to past research. Another important consideration is whether social distance validly taps the stigma construct.…”
Section: Feldman and Crandallmentioning
confidence: 68%
“…As mentioned previously, the vignettes were designed to depict the modal gender and symptom profile, average age range of onset, most common treatment, and usual prognosis for each target individual. Second, vignette methodologies are widely employed in the stigma literature (e.g., Ben Porath, 2002;Corrigan et al, 2005;McBride, 1998;Schumacher, Corrigan, & Dejong, 2003;Schwartz, Weiss, & Lennon, 2000;Walkup, Cramer, & Yeras, 2004), rendering the results of the present study readily comparable to past research. Another important consideration is whether social distance validly taps the stigma construct.…”
Section: Feldman and Crandallmentioning
confidence: 68%
“…25,26 Case vignettes have been used for measuring physicians' practice patterns and have gained considerable support because of their predictive value of physician behaviour. [27][28][29][30][31] Investigators have found that physicians' responses to cases are a good indication of what they will actually do in a clinical setting. Kelly and colleagues 1 used case vignettes to assess physician attitudes concerning HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of multiple stigmatized identities recognizes that individuals might have more than one stigmatized identity affecting their health, health beliefs, and health behavior (Sangaramoorthy et al, 2017; Turan et al, 2019). Prior work on the “double jeopardy” hypothesis (Berdahl & Moore, 2006; Turan et al, 2019)—which reported higher prejudice and discrimination toward individuals with multiple (vs. single) stigmatized identities—in Western countries found that individuals with mental illness are more stigmatized when they are minority (vs. majority) group members (McGuire & Miranda, 2008; Staiger et al, 2018 but see Walkup et al, 2004). However, whether these individuals would also be more stigmatized in Eastern countries, and if so why that might be, remains unknown.…”
mentioning
confidence: 99%